RETRACKTED: ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS XI MIPA SMA NEGERI 4 PEKANBARU TAHUN AJARAN 2021/2022 - Desi Lestari; Mellisa Mellisa (Bioilmi: Jurnal Pendidikan, 2023)
The revocation note is entitled "Revocation [Analisis Faktor Yang Mempengaruhi Minat Belajar Siswa Pada Mata Pelajaran Biologi Kelas XI MIPA SMA NEGERI 4 Pekanbaru Tahun Ajaran 2021/2022]” which has been published in Bioilmi: Jurnal Pendidikan Volume 9, Number 2, 2023. There has been a violation of the professional code of ethics, namely double submission in another journal and has been published in the Journal of Perspektif Pendidikan Dan Keguruan Volume 14, Number 3, 2023. Here is the link the journal; https://journal.uir.ac.id/index.php/Perspektif/article/view/11238 The retraction of the article by the Editor has been approved by the author. This is important to do because plagiarism violations occur.We as managers of Bioilmi: Jurnal Pendidikan, hope that this incident of violation of the code of ethics can be resolved.